2018
DOI: 10.1257/pandp.20181075
|View full text |Cite
|
Sign up to set email alerts
|

Applying Generalized Pareto Curves to Inequality Analysis

Abstract: A generalized Pareto curve is defined as the curve of inverted Pareto coefficients b(p), where b(p) is the ratio between average income or wealth above rank p and the p-th quantile. We present this concept and show how it can be used to better estimate distributions, especially from tax tabulations. By providing a simple decomposition of top shares, we discuss how studying inverted Pareto coefficients can improve the understanding of inequality dynamics. We also show how it helps to better analyze wealth and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…REDI is a resource for researchers particularly interested in top incomes. The method estimates top incomes without relying on the Pareto distribution, an advantage since true income distributions deviate in important ways from this idealized model (Hout 2004;Blanchet et al 2018).…”
Section: Advantages Of the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…REDI is a resource for researchers particularly interested in top incomes. The method estimates top incomes without relying on the Pareto distribution, an advantage since true income distributions deviate in important ways from this idealized model (Hout 2004;Blanchet et al 2018).…”
Section: Advantages Of the Methodsmentioning
confidence: 99%
“…This is an arbitrary but convenient assumption (von Hippel et al 2016). Nonetheless, it has been shown that the Pareto REDI for Binned Data distribution is an inexact fit to this upper tail (Hout 2004;Blanchet et al 2018). This is important because even small errors in defining this distribution will result in large errors in estimating the variance and other parameters (Jargowsky and Wheeler 2018).…”
Section: Dealing With Top and Bottom Incomesmentioning
confidence: 99%
“…Theoretically, it has been known that the generalized Pareto distribution is a fairly general family that includes the Pareto distribution and the exponential distribution as two special cases (Balkema and Haan, 1974;Pickands, 1975;Singh and Maddala, 1976;Cowell, 2000). In this regard, Blanchet et al (2017Blanchet et al ( , 2018 used the generalized Pareto distribution to describe the income structure of the total population, where the generalized Pareto distribution is defined as follows:…”
Section: Exponential Income Distributionmentioning
confidence: 99%
“…Clementi et al, 2012;Prinz, 2016;Irwin and Irwin, 2017;Rosser, 2019;Tao et al, 2019;Ma and Ruzic, 2020) and the top income class (less than 5% of populations) follows a Pareto distribution (Mandelbrot, 1960;Nirei and Souma, 2007;Atkinson et al, 2011;Aoki and Nirei, 2017;Tao et al, 2019). In this regard, Blanchet et al (2017Blanchet et al ( , 2018 have used the generalized Pareto distribution to describe the income structure of the total population. The generalized Pareto distribution is a fairly general family that includes the Pareto distribution and the exponential distribution as two special cases (Singh and Maddala, 1976;Cowell, 2000;Jenkins, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence had covered more than 66 countries 19 , ranging from Europe to Latin America, North America, and Asia. Recently, Blanchet et al [4][5] proposed to use the generalized Pareto distribution to describe the income structure of the total population, where the generalized Pareto distribution is defined as follows 1-3 :…”
mentioning
confidence: 99%